Does Health Education Really Matter? Evaluating the Role of Health Education in Improving Anemia Knowledge in Adolescent Girls - Ayu, Windri Dewi; Setyawati, Anita; Jaelani, Ahmad (CV. Strata Persada Academia, 2025)
Anemia remains a significant global health issue, particularly among adolescents, where its prevalence threatens both individual well-being and national development. This study evaluates the impact of health education on improving anemia knowledge among 32 adolescent girls at SMPN 2 Majalengka. Using a quasi-experimental approach, pretest and posttest questionnaires assessed participants' knowledge before and after a structured health education program. The intervention included lectures and discussions covering anemia's definition, symptoms, risk factors, impacts, prevention, and treatment. Results revealed a notable improvement in knowledge, with the proportion of respondents scoring in the